AUDIT KINERJA PROSES PENGOLAHAN PADA PABRIK GULA - Sartika, Nyimas Dewi (Industrial and Systems Engineering Assessment Journal (INASEA), 2005)
Generally on BUMN sugar factory the rendement is lower than private sugar factory. The audit purpose is to know processing system description and hopefully will be able to deliver suggestion and recommendation to management to improve the processing system. Auditee is one of BUMN sugar factory in East Java with 3000 TCD (ton cane per day) milling capacity, Auditee produce sugar with 6, 20% average rendement and side product such as, bagasse, molasses, and blotong. According to the audit we can conclude the low rendement is caused by low quality of sugar cane plant and processing system on the factory.